MICROFINANCE ET LUTTE CONTRE LA PAUVRETE EN REPUBLIQUE DEMOCRATIQUE DU CONGO : UNE ANALYSE CRITIQUE - NGANDI, Alphonse LIOTO (IJRDO - Journal of Business Management, 2021)
In this article, we present the issue of microfinance in the process of poverty reduction in the DRC. Indeed, everyone knows that the fight against poverty is a very delicate stage which requires appropriate strategies in order to improve the well-being of the population. It is in this sense, microfinance which is considered as a financial instrument in the service of the poor can be favorable to help the low-income population in the DRC to improve their living conditions and their households. It has been observed that microfinance has been very successful in certain developing countries such as (… ..). Its beneficial effects are noted above all by increasing the income of micro-entrepreneurs and empowering women. Nowadays, it is arguably another appropriate source of finance for poor populations who do not have access to bank credit. However, we have observed that in the Democratic Republic of Congo its effectiveness remains very modest or even mixed, especially in building the capacities of beneficiary populations. Microfinance does not seem to effectively improve the living conditions of these beneficiaries. This is why, in this article, we will analyze some of our observations about the issue of microfinance in the DRC. We will then explain the economic theory of microfinance. It should be noted that the analysis of this dissertation is the synthesis of the introductory part and the first chapter of our doctoral research theme. Thus, the questions that raise the need to undertake this research are as follows:Can microfinance effectively fight against poverty in the Democratic Republic of Congo?What is its impact on the standard of living of these beneficiaries and their households?